To make a study and to set up an experimental electroplating unit / Norulhuda Mohamad Adam - Mohamad Adam, Norulhuda (1981)
As an initial phase, only, the pre-treatment process (ddegreasing, electrolytic degreasing and acid pickling), copper plating and nickel plating experimental units were set-up. Copper plating was used only as an undercoating process prior to nickel plating.